Elevated lipid peroxides induced angiogenesis in proliferative diabetic retinopathy - Saxena, Sandeep (Springer-Verlag, 2011)
Oxidative stress is associated with causation of diabetic vascular complications. A case–control study was undertaken to evaluate the association of platelet thiobarbituric acid reacting substances (TBARS) with the severity of diabetic retinopathy for the first time. Platelet TBARS levels were estimated using standard protocol. Platelet TBARS levels in the cases with non-proliferative diabetic retinopathy, proliferative diabetic retinopathy, and healthy controls were 0.56 ± 0.09, 0.69 ± 0.11 and 0.41 ± 0.1 nmol/h/10(8) platelets, respectively. A significant increase in platelet TBARS levels was observed in the cases as compared to controls (p < 0.001). Elevated TBARS levels were observed to significantly increase further during the proliferative stage of the disease (p < 0.01). The increase in platelet TBARS levels, and thereby at retinal level, is associated with angiogenesis in diabetic retinopathy. Supplemental anti-oxidant therapy in diabetic retinopathy may prevent ocular angiogenesis resulting as a consequence of oxidative stress.